2004
DOI: 10.1111/j.0030-1299.2004.13510.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of genetic markers to quantify bumblebee foraging range and nest density

Abstract: Bumblebees (Hymenoptera: Apidae) are important pollinators of crops and wildflowers, but many species have suffered dramatic declines in recent decades. Strategies for their conservation require knowledge of their foraging range and nesting density, both of which are poorly understood. Previous studies have mainly focussed on the cosmopolitan bumblebee species Bombus terrestris, and implicitly assume this to be representative of other species. Here we use a landscape-scale microsatellite study to estimate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
233
3
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 192 publications
(251 citation statements)
references
References 36 publications
13
233
3
2
Order By: Relevance
“…S3). This result is consistent with results obtained with bumblebees (24,35) and honeybees (36,37), which indicate that bees usually do not forage very close to their nests (1), even if this should not be true for every bee species (38).…”
Section: Discussionsupporting
confidence: 90%
“…S3). This result is consistent with results obtained with bumblebees (24,35) and honeybees (36,37), which indicate that bees usually do not forage very close to their nests (1), even if this should not be true for every bee species (38).…”
Section: Discussionsupporting
confidence: 90%
“…The method is usually employed to study social organisms (e.g. Rossiter et al 2002;Darvill et al 2004;Tó th et al 2008), but here is shown that the technique can be readily used to study host selection and foraging in insects.…”
Section: Discussionmentioning
confidence: 99%
“…These characteristics play an important role for the structure and dynamics of plant-pollinator networks. Large body size reflects the capacity to fly longer distances, and genetic markers and radio-tracking techniques are increasingly used to estimate actual flight distances (Darvill et al, 2004;Hagen et al, 2011). Small stingless bees (e.g.…”
Section: Box 4 Bees As Network Nodesmentioning
confidence: 99%